The sorption/chromatography hypothesis of olfactory discrimination: The rise, fall, and rebirth of a Phoenix. (5th January 2022) - Coppola, David M.
Abstract: Herein, I discuss the enduring mystery of the receptor layout in the vertebrate olfactory system. Since the awarding of the 2004 Nobel Prize to Axel and Buck for their discovery of the gene family that encodes olfactory receptors, our field has enjoyed a golden era. Despite this Renaissance, an answer to one of the most fundamental questions for any sensory system—what is the anatomical logic of its receptor array?—eludes us, still, for olfaction! Indeed, the only widely debated hypothesis, finding its origins in the musing of another Nobel laureate Sir Edgar Adrian, has it that the vertebrate nose organizes its receptors according to the "sorptive" properties of their ligands. This idea, known as the "sorption" or "chromatography" hypothesis, enjoys considerable support despite being controversial. Here, I review the history of the hypothesis—its rises and falls—and discuss the latest data and future prospects for this perennial idea whose history I liken to the mythical Phoenix. Abstract : The sorption or chromatography hypothesis of olfaction posits that odorant discrimination is be based in part on spatial patterns of odorant distribution across the olfactory sensory neuron array caused by water solubility. This essay explores the specific claims of this long‐standing hypothesis and the evidence for and against them.